STUDY ON THE EFFECT OF POLLUTANTS ON THE PRODUCTION OF AAPTAMINES AND THE CYTOTOXICITY OF CRUDE EXTRACT FROM Aaptos suberitoides - Dewi, Ariyanti Suhita; Hadi, Tri Aryono; Januar, Hedi Indra; Pratitis, Asri; Chasanah, Ekowati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
This experiment was conducted to study the effects of anthropogenic stressor on the spatialvariability of secondary metabolites from marine sponge Aaptos suberitoides. Samplings wereconducted at 7 sites in Marine National Park of Thousand Islands that are extended within 30 kmoff Jakarta bay on late February 2011. Sponges were collected and quantified by means of liquidchromatography coupled with photo-diode array detection, whereas, cytotoxicity of sponges extractswas determined against T47D (breast) cancer cell lines. Results showed that the spatialproduction of aaptamine and isoaaptamine did not correlate with the quality of their surroundinghabitat, despite nitrite and nitrate levels significantly affected the bioactivity of crude extracts.